THE INFLUENCE OF BRAND IMAGE AND SOCIAL STUDENTS ENVIRONMENT ON THE INTEREST TO BE A CUSTOMER OF INDONESIAN SHARIA BANK WITH KNOWLEDGE AS A MODERATING VARIABLE - Mhd Adjie Massad; Nurbaiti; Nur Ahmadi Bi Rahmani (Sharia Banking Study Program, Faculty of Islamic Economics, Djuanda University, Bogor, 2023)
The low interest of the Indonesian people in utilizing Islamic banks is the driving force behind this research. This is indicated by the market share of Islamic banking of 6.52 per cent in 2021. With knowledge as a moderator variable at UIN Sumatra Utara (student case study), this study aimed to determine the effect of a person's social environment and brand image on their desire to save in Islamic banks. This study uses quantitative survey questionnaire data and smartPLS software for PLS (Partial et al.) analysis. This study had 100 respondents who were all students of UIN Sumatra Utara. Practical sampling was used to select individual categories, and non-probability sampling was used. The research findings show that a person's social environment impacts their willingness to save in Islamic banks; However, a person's brand image does not impact their desire to save in an Islamic bank, and there is no knowledge moderating variable. By adjusting the influence of this brand image, Islamic banks can moderate the influence of the social environment on the willingness to save. It is hoped that UIN Sumut students will be more interested in information and brands related to Sharia banking, especially those targeting Muslims, as a result of this finding. They will be able to switch to Islamic banking products recommended by the Qur'an and Hadith, and they will also be able to allow other researchers to look for additional independent variables that were not examined in this study and identify population groups that are different from one another.